Efecto de tres dosis de 6- benciladenina en el incremento de la floración de Piñón Blanco (Jatropha curcas L.) – Juan Guerra – San Martín – Perú - Córdova Mendoza, Eyka Sugeire (2016)
This following research had the aim to evaluate and to determinate the doses of 6 – Benziladenine (BA) increasing flowering and fruit yields of Physic nut in “El Porvenir” Experimental Research Center, and performing an economic analysis of each treatment. The research was carried out in “El Porvenir” Experimental Research Center located in Juan Guerra district, province and region of San Martin. A randomized block design (RBD) was used in a factorial array of three doses of BA and two flowering phases (A1 and A2). The evaluated variables were: number of female flower per inflorescence, number of male flowers per inflorescence, number of hermaphrodite flowers per inflorescence, number of fruits per raceme, weight of seed per plant, yield (kg.ha-1) and economic analysis. The results shows that a BA dose of 240 ppm tends to stimulate a higher number of female flowers per inflorescence (28,9), higher number of fruit per raceme (25,8); However, because of weather variation, the previously mentioned dose did not affect the seed weigh nor yield turning into a negative cost-benefit rate